The interrelated roles of RAB family proteins in the advancement of neoplastic growth - Yuxin Ji; Yuxin Ji; Ruonan Li; Ruonan Li; Guohui Tang; Guohui Tang; Wenrui Wang; Wenrui Wang; Changjie Chen; Changjie Chen; Qingling Yang; Qingling Yang; et al. (Frontiers in Oncology)
Rab Proteins, A Subfamily Of The Ras Superfamily Of Small Gtpases, Are Critical Regulators Of Intracellular Vesicular Trafficking, Which Is Intricately Linked To Various Cellular Processes. These Proteins Play Essential Roles Not Only In Maintaining Cellular Homeostasis But Also In Mediating The Complex Interplay Between Cancer Cells and Their Microenvironment. Rab Proteins Can Act As Either Oncogenic Factors Or Tumor Suppressors, With Their Functions Highly Dependent On The Cellular Context. Mechanistic Studies Have Revealed That Rab Proteins Are Involved In A Variety Of Processes, Including Vesicular Transport, Tumor Microenvironment Regulation, Autophagy, Drug Resistance, and Metabolic Regulation, and Play Either A Promotional Or Inhibitory Role In Cancer Development. Consequently, Targeting Rab Gtpases To Restore Dysregulated Vesicular Transport Systems May Offer A Promising Therapeutic Strategy To Inhibit Cancer Progression. However, It Is Equally Important To Consider The Potential Risks Of Disrupting Rab Functions, As Their Roles Are Highly Context-Dependent and May Have Opposing Effects In Different Malignancies. This Review Focuses On The Multifaceted Involvement Of Rab Family Proteins In Cancer Progression Underscores Their Importance As Potential Therapeutic Targets and Underscores The Need For A Deeper Understanding Of Their Complex Roles In Tumorigenesis.